2005
DOI: 10.1080/17408980500340885
|View full text |Cite
|
Sign up to set email alerts
|

Once more with feeling: affect and playing with the TGfU model

Abstract: Certainly, the process of decision-making and problem-solving in a shifting playing environment lies at the core of the Teaching Games for Understanding (TGfU) model. What is not clear is how, at the time of decision-making, players' feelings or affective factors and their subsequent influence on thinking, influence these processes. Affect has a number of constitutive elements, namely feeling, choice, emotion and preference. More importantly affect is linked inseparably to cognition and because it functions si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
0
18
0
14
Order By: Relevance
“…As these authors reported the biggest impact on learning occurred when students had learnt to learn through Cooperative Learning, it serves the field to know more about the learning outcomes that result from sustained use of the model. Furthermore, while the affective domain may have received a lack of attention due to the impersonal and subjective nature of this form of learning (Pope, 2005), we would also argue that learning in this domain takes time to develop. This claim has plausibility when you consider that most studies reviewed reported that the three other learning domains were developed: even in shorter units (lasting 12-14 lessons or less) and when they were not the prominent feature of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these authors reported the biggest impact on learning occurred when students had learnt to learn through Cooperative Learning, it serves the field to know more about the learning outcomes that result from sustained use of the model. Furthermore, while the affective domain may have received a lack of attention due to the impersonal and subjective nature of this form of learning (Pope, 2005), we would also argue that learning in this domain takes time to develop. This claim has plausibility when you consider that most studies reviewed reported that the three other learning domains were developed: even in shorter units (lasting 12-14 lessons or less) and when they were not the prominent feature of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Affective learning was rarely noted as a prominent feature of investigation. These limited accounts of the 'psychological' aspect of learning, and the perhaps misleading evidence exploring the psychological aspects of learning, seem to highlight Pope's (2005) argument that affective learning is somewhat challenging to define due to its subjective and personal nature.…”
Section: Affective Learningmentioning
confidence: 99%
“…Outros recursos importantes para fazer o balanço e apreciar as tendências de desenvolvimento da investigação e da reflexão teórica e das propostas práticas sobre o TGfU são os livros "Teaching games for understanding in physical education and sport" (21) , que resultou da primeira edição da conferência TGfU, em 2001, e mais recentemente "Teaching Games for Understanding: theory, research, and practice" (67) . Recentemente também, a revista Physical Education and Sport Pedagogy publicou um número dedicado ao TGfU, editado por Richard Light (101) e constituído por artigos desenvolvidos a partir de apresentações à conferência TGfU de Melbourne (2,20,64,66,102,130) O modelo TGfU não é um modelo cristalizado, entendido como algo que atingiu a sua forma perfeita e acabada. É um modelo aberto ao diálogo com diferentes perspectivas teóricas sobre o curriculum, a instrução, a relação pedagógica e a aprendizagem, com preponderância para as diversas perspectivas cognitivistas e construtivistas, mais ligadas às teorias do processamento da informação (15,68,174) , às perspectivas construtivistas de pendor mais piagetiano ou radical (19,61,138) , de pendor mais vygotskiano, social e cultural (33), como a teoria da aprendizagem situada (90,91,93,100,102) .…”
Section: Figura 1 Modelo De Ensino Dos Jogos Para a Compreensão (Tgfunclassified
“…Outro contributo para a revisão do TGfU proveio de Holt, Strean e Bengochea (82) , clamando para que o TGfU estenda as suas preocupações ao domínio sócio afectivo, dê espaço à emoção, ao sentimento, ao prazer e não se quede apenas pela compreensão e pela execução do movimento. Em sentido semelhante argumentaram Pope (130) , na defesa de uma releitura afectiva do modelo TGfU, e Kretchamar (94) , na defesa do domínio subjectivo, do significado da experiência e do deleite, que é mais exigente, mas mais memorável e mais profundo que as experiên-cias divertidas.…”
Section: Figura 1 Modelo De Ensino Dos Jogos Para a Compreensão (Tgfunclassified
“…Kirk & Macdonald, 1998;Light, 2011;Pope, 2005;Ward & Lee, 2005; for overviews see Amade-Escot, 2006;Rovegno, 2006;Rovegno & Dolly, 2006). Kirk, Macdonald, and O'Sullivan (2006) define the field of physical education (PE) and sport pedagogy as being framed by three intertwined key elements: learning, teaching and curriculum.…”
Section: Introductionmentioning
confidence: 99%